Methodology to assess organizational climate - Ada de la C. Tamayo-Monagas; Jorge Olivares-Boada; Manuel Lozano-Diéguez (Universidad de Guantánamo, 2016)
The work recommends a methodological tool to evaluate the Organizational Climate that allows socio-psychological actions of continuous improvement in the environment and organizational development. The theme responds to one of the priorities of the Institutional management to offer a service of excellence in order to reinforce innovation, commitment to the continuous improvement of the organization, the personal and group development of the members of it, and for achieving the goals and objectives of the organization. The main theories of Organizational Climate as well as their manifest interrelation are necessary, and their main approaches and methodologies are discussed. The paper offers the theoretical and methodological foundations of the proposal and its practical conception. Emphasis is given to integrated structural and systemic approaches and to the treatment of Organizational Climate through the operational concept. Finally, the effectiveness of the methodological proposal is set, based on the evaluation and critical revision of experts.